Seasonal Slumps in Juventae Chasma, Mars. Issue 10 (30th October 2017) - Ojha, Lujendra; Chojnacki, Matt; McDonald, George D.; Shumway, Andrew; Wolff, Michael J.; Smith, Michael D.; McEwen, Alfred S.; Ferrier, Ken; Huber, Christian; Wray, James J.; Toigo, Anthony
Abstract: Dark topographic slumps several meters wide, tens of meters in length, and up to a meter in depth are observed on the slopes of Juventae Chasma (JC), Valles Marineris (VM), Mars. These slumps usually originate near the terminal points of recurring slope lineae (RSL). Near their initiation points, the slumps have topographic depressions due to the removal of materials; near their lowermost reaches, new materials are deposited in lobes. Over the course of three Mars years, 10 active slumps have been observed in JC, all of which formed in or near the same season (areocentric longitude: Ls 0°–120°). Mars Color Imager (MARCI) observations show low‐altitude atmospheric obscurations confined within the topography of the VM and JC in the seasons when the slumps form. In one instance, data from the Compact Reconnaissance Imaging Spectrometer for Mars and MARCI show evidence of H2 O ice in the atmospheric obscuration, likely due to the formation of a low‐level afternoon cloud above a dust storm, or mixing of condensate clouds with a diffuse dust cloud. The presence of atmospheric obscurations with H2 O ice near times when the slumps form is intriguing, but no direct evidence currently exists to support that they aid in slump formation. Further monitoring of this site will help establish if RSL and/or atmospheric events play a role in the creation of contemporary slumps. Key Points: Dark topographic slumps are observed on the slopes of Juventae Chasma on Mars Ten active slumps have been observed in JC, all of which formed in or near the same season Intriguing spatial and temporal correlations with recurring slope lineae and atmospheric obscurations are observed